Accelerated T1rho relaxation quantification in intervertebral disc using limited spin-lock times - Wang, Yi-Xiang J (AME Publishing Company, 2013)
OBJECTIVE: T1rho relaxation measurement has the potential to identify early biochemical changes in the intervertebral disc. Traditionally, multiple spin-lock times (SLT), often ~5 SLTs, are used to ensure the accuracy and robustness of T1rho mapping. It will be advantageous to use fewer SLT points if comparable accuracy of T1rho mapping can be achieved. In this study, the feasibility of using 3 SLT points to measure intervertebral disc T1rho relaxation time is explored. MATERIALS AND METHODS: The lumbar spine of 12 subjects (age range: 30-75 years, disc =60) were studied on 3-T MRI. For T1rho measurement, a rotary echo spin-lock pulse was implemented in a 3D balanced fast field echo (b-FFE) sequence. Spin-lock frequency was set as 500 Hz and the SLTs of 1, 10, 20, 40, and 60 ms were acquired. T1rho maps were generated by fitting each pixel’s intensity as a function of SLT using a non-negative least-square fitting algorithm. Images were analysed in the mid-sagittal section. T1rho maps were re-constructed using all 5 SLT points of 1, 10, 20, 40, and 60 ms, and three SLT points of 1, 20, and 60 ms respectively. ROIs included nucleus pulposus (NP), anterior annulus fibrosus (AF) and posterior annulus fibrosus. Values of anterior AF and posterior AF were averaged as the value for AF. Agreement of T1rho measurements using different SLT points was assessed using intra-class correlation coefficient (ICC) on absolute agreement as well as Bland and Altman plot. RESULTS: There was no significant difference for T1rho values by 5-SLT measurement and 3-SLT measurement in both NP (P=0.63) and AF (P=0.31). The ICC for 5-SLT T1rho measurement vs. 3-SLT T1rho measurement was 0.991 and 0.981 respectively for NP and AF T1rho time. The Bland and Altman plots for the comparison showed a mean difference of 3.14 and 1.83 for NP and AF respectively. Polling the T1rho values for NP and AF in 60 discs together, the ICC for 5-SLT T1rho measurement vs. 3-SLT T1rho measurement was 0.993, and the Bland and Altman analysis showed a mean difference of 2.56. CONCLUSIONS: This study suggests that adopting 3 SLTs of 1, 20, and 60 ms can be an acceptable alternative for the disc T1rho measurement.